Optimization of Gelatin Extraction from the Skin of Freshwater Carps by Response Surface Methodology - Ninan, George; A.A., Zynudheen; P.T., Mathew; V., Geethalakshmi (Fishery Technology, 2025)
Response Surface Methodology (RSM) was used to determine the optimum operating conditions for extracting the gelatin from the skin of three species of freshwater carps viz., Rohu(Labeo rohita). Common Carp (Cyprinus carpio) and Grass Carp (Ctenopharyngodon idella). From the screening experiments, four independent variables viz., alkali pretreatment concentration, acid pretreatment concentration, pretreatment time and extraction temperature were identified as the critical variables that had significant effect on the extraction of gelatin from the skin of these species. The responses studied were gel strength and yield. The optimum gelatin extraction conditions from the skin of three species based on the responses were 51.35 minutes (pre-treatment time) and 49.330C (extraction temperature) for Rohu skin; 60 minutes (pre-treatment time) and 57.970C (extraction temperature) for Common Carp skin; 60 minutes (pre-treatment time) and 400C (extraction temperature) for Grass Crap skin. The gelatin from the skin of the freshwater carps showed high yield, medium gel strength and high viscosity.